S.Y. Witte about labour of J. M. Hordyeyenko «Bases of railway economy» it is Saint Petersburg, 1885» - Petruchenko, O. A. (History of science and technology, 2016)
In the article view edthe review of S. Witteon text book of Professor J.M.Hordyeyenko «Fundamental sof railway economy» (1885). Actually, S.Y. Witte wrote not many scientific articles. However, the textbook of J. M. Hordyeyenko impressed him so much especially those problems, whichwas touched by the author, so Sergei Witte expressed his opinion on the author`sopening lecture,devoted to rail tariffs and rail transportation. The opinion S.Y. Witte is highly relevant even today.